Characterization of the Caput Mortuum purple hematite pigment and synthesis of a modern analogue. (February 2021) - Castagnotto, Elena; Locardi, Federico; Slimani, Sawssen; Peddis, Davide; Gaggero, Laura; Ferretti, Maurizio
Abstract: This investigation addressed the characterization and the production methods of the purple pigment Caput Mortuum used since pre-historic times until the eighteenth century. Literature hypotheses for its production after heating of ochres/Fe-hydroxides, with addition of white minerals of different composition has been experimentally reproduced, and disproved. An original synthesis after massive hematite that underwent fine grinding, followed by high temperature (900–1100 °C) annealing under oxidative conditions was carried out. Several natural and synthetic starting Fe-oxides and hydroxides were tested with these procedures, followed by compositional (X-Ray Powder Diffraction), spectroscopic (Reflectance spectroscopy, colorimetric measurements and Lab CIE color space), microscopic (Scanning Electron Microscopy coupled with Energy Dispersive Spectrometry), and magnetic characterization. The color changes undergone by hematite from red to purple could be mainly traced back to the grain dimensions resulting from the annealing process. The experiments on synthetic starting materials allowed excluding that the final color is affected by impurities. Moreover, it was determined that a purple ochre could not be obtained by thermal treatment of natural earths and that the purple pigment could only be manufactured by starting from hematite and not from red ochre. Finally, magnetic measurements further discriminated among different Caput Mortuum types. Graphical abstract: Image 1 Highlights: The rare purple pigment Caput Mortuum was addressed with a multimethod characterization. The starting materials were natural and synthetic ochers and Fe-oxides and hydroxides. Fine grinding was followed by high T annealing under oxidative conditions. Purple hue derives from high-purity hematite, not from Fe-poor ochres.